Development and evaluation of an observational system for goalball match analysis - Márcio Pereira Morato; Otávio Luis Piva da Cunha Furtado; Diego Henrique Gamero; Thiago Pinguelli Magalhães; José Júlio Gavião de Almeida
Abstract Our purpose was to develop and evaluate an observational system for goalball match analysis. We used a non-participant systematic game observation method including eight elite games, video recorded, and randomly chosen. Observational categories and performance indicators were determined for each offensive (i.e., ball control, attack preparation, and throwing) and defensive principles (i.e., defensive balance, throw reading, and blocking). The comprehensive method of development and the ideal reliability levels (kappa coefficient of 0.81-1.00) of this protocol ensure the generation of quantitative and qualitative information for players and coaches and the rigor required for scientific use.